Validation of the Clinical Frailty Scale for the Prediction of Mortality in Patients With Liver Cirrhosis. Issue 7 (21st July 2020) - Kremer, Wolfgang M.; Nagel, Michael; Reuter, Michael; Hilscher, Max; Michel, Maurice; Kaps, Leonard; Labenz, Joachim; Galle, Peter R.; Sprinzl, Martin F.; Wörns, Marcus-Alexander; Labenz, Christian
Abstract : INTRODUCTION: Frailty is a common but often underestimated complication in patients with liver cirrhosis. The Clinical Frailty Scale (CFS) allows the assessment of frailty within a short period of time but has only been investigated in a Canadian cohort of outpatients. The aim of the current study was to evaluate the ability of the CFS to predict mortality in outpatients and nonelectively hospitalized German patients. METHODS: Two hundred outpatients and 99 nonelectively hospitalized patients with liver cirrhosis were prospectively enrolled. Outpatients/inpatients were followed for a median of 364/28 days regarding the primary outcome of death or liver transplantation. Eighty-seven patients of the outpatient cohort and 64 patients of the inpatient cohort had available computed tomography-scans for the quantification of muscle mass. RESULTS: Median CFS was 3 in the outpatient and the inpatient cohort. Twenty-one (10.5%) outpatients were at least prefrail (CFS > 3) and 26 (26.3%) inpatients were frail (CFS > 4). For every one-unit increase, there was an independent association between the CFS and mortality in the outpatient cohort (hazard ratio 1.534, P = 0.007). This association remained significant after controlling for muscle mass in the subcohort with available computed tomography scans. In the inpatient cohort, frailty (CFS > 4) was an independent predictor for 28-day mortality after controlling for acute-on-chronic liver failure, albumin, and infections (odds ratio 4.627, P = 0.045). However, this association did not reach significance in a subcohort after controlling for muscle mass. DISCUSSION: Especially in outpatients, CFS is a useful predictor regarding increased mortality independent of the muscle mass.